The Effects Of The Station Rotation Model On Libyan Secondary School Students’ Efl Writing Skills: Teachers’ And Students’ Perceptions - Salem Albelazi, Najah Abdullah (2022)
Educational technology is often used to improve educational processes in the modern digital age. Although secondary schools in Libya have minimal amenities, teachers have not been formally encouraged or practised using technology. Similarly, there is no demonstration of how technology can help high school pupils enhance their writing skills. The main goal of this study was to examine if involving students in a Station Rotation Model (SRM), utilising a blended learning approach, may help them enhance their writing essays skills. The following research questions were addressed: (1) To what extent does the SRM affect Libyan EFL secondary students’ performance in writing? (2) What are the teachers’ perceptions of the use of the SRM to teach writing? and (3) What are the Libyan EFL Secondary students’ perceptions of the use of the SRM in teaching writing skills? In this study, 2 EFL Libyan teachers, and 55 students from two classes of the second year (28 students in the experimental group class) and (27 students in the control group class) in a Libyan secondary school in Al Khums participated in a mixed-methods design research. The data were collected by applying pre-post and delayed tests, class room observations, teachers’ interviews and focus group interviews.